Policy framework on tourism development for heritage sites the case of Romblon - Soliman, Elmer Jr. M.; Lico, Gerard Rey A. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Heritage sites are places that reflect its civilization's history and culture. The value that it contributes to the society goes beyond its economic and social importance. With this in mind, several regulations are put in place to ensure the conservation and promotion of these heritage sites, one of which involves protecting its cultural identity. In various places in the world, heritage sites are one of the well-preserved treasures that each country takes pride in. Heritage sites generate interests, and interests attract tourism. Undeniably some sites are experiencing a good economic status dues to the influx of tourists. For them, one of the best ways to strive for economic growth is to open their place to the visitors while introducing their rich culture and history. Part of tourism growth is the influx of tourists and with it, the influx of investments in tourism infrastructure as well as the integration of new activities that transform an untouched place into a busy one. The transition stage from being a secluded peaceful area to being a public place is now the concern. Moreover, the impact of these developments to the significance and integrity of these sites is worth studying in order to establish guidelines and regulatory measures. The primary goal of the study is to show the positive and negative effects of tourism to Heritage sites through, documentary analysis and key person interviews, where concerned institutions are visited to facilitate the request for pertinent documents and the interviews to department heads and other resource persons. Fieldwork and on-site inspection are likewise conducted on selected heritage sites. Survey forms were also deployed to locals and tourists alike, pertaining to their activities before and after the rise of tourism. The final output of the study is a policy framework for cultural tourism in the town of Romblon. This framework was developed based from the results of the survey, interviews, observation, and the technical know-how of the researcher gained through views of existing laws, guidelines, and similar developments happening in other tourism destination.
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Tourism -- Philippines